Role of Inventory Visibility on Performance of Manufacturing Sector in Sub-Saharan Africa: A Study in Kenya - Benedict Mutinda Kimwaki (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
Inventory visibility is the ability of an organization to streamline its inventory tracking methods so as to ensure the right amount inventory is stocked based on the customers’ needs and the supply rates of the suppliers. Having a high degree of inventory visibility is increasingly seen as a competitive advantage in modern supply chain management, as it allows for greater agility and responsiveness to market changes. One of the compelling issues that have been facing the manufacturing industry in Kenya is the inability to meet customer demands and high waiting times. Previous literature has shown that with a visible inventory, manufacturing firms could enhance their delivery effectiveness and significantly reduce waiting time. This however lacks empirical backing from a Kenyan perspective, hence the subject of the study. The study was anchored on the transaction cost theory. Descriptive research design was adopted, and the large manufacturing firms in Kenya were targeted. A sample of 160 firms was selected. Through a structured questionnaire, primary data was collected from the heads of supply chain in the 160 companies. The findings revealed that inventory visibility is an instrumental determinant of the performance of the manufacturing industry in Kenya. It was established that inventory visibility enabled manufacturing companies to have real-time or near-real-time information about the quantity, location, and status of its products or goods throughout the supply chain. This allowed for accurate tracking and management of inventory levels, which is crucial for efficient operations and customer satisfaction.